2022
DOI: 10.3390/antibiotics11020157
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genomic Insights of mcr-1-Producing Escherichia coli Isolates from Piglets

Abstract: The use of colistin in food-producing animals favors the emergence and spread of colistin-resistant strains. Here, we investigated the occurrence and molecular mechanisms of colistin resistance among E. coli isolates from a Mexican piglet farm. A collection of 175 cephalosporin-resistant colonies from swine fecal samples were recovered. The colistin resistance phenotype was identified by rapid polymyxin test and the mcr-type genes were screened by PCR. We assessed the colistin-resistant strains by antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Although the location of all ARGs couldn't be confirmed due to short length sequencing, this study identified a 288 kb megaplasmid of highly transferable IncHI2 family that carries ARGs conferring resistance to aminoglycosides {aadA2, ant (3")-IIa, aph(3')-IIa, aph(3")-Ib, aph(6)-Id}, phenicols (cmlA1), sulfonamides (sul1, sul3), tetracyclines (tetA, tetR) and trimethoprims (dfrA15). Occurrence of MDR with mcr-1 E. coli has been reported earlier [9,47], however, rats carrying these types of resistance determinants on plasmids are firstly reported in this study to the best of our knowledge. Occurrence of MDR E. coli carrying ARGs on horizontally transferable elements is worrisome and imposes a potential threat of transferring and disseminating these resistance determinants to human and animals through contaminated food, water and environment.…”
Section: Plos Onementioning
confidence: 50%
See 1 more Smart Citation
“…Although the location of all ARGs couldn't be confirmed due to short length sequencing, this study identified a 288 kb megaplasmid of highly transferable IncHI2 family that carries ARGs conferring resistance to aminoglycosides {aadA2, ant (3")-IIa, aph(3')-IIa, aph(3")-Ib, aph(6)-Id}, phenicols (cmlA1), sulfonamides (sul1, sul3), tetracyclines (tetA, tetR) and trimethoprims (dfrA15). Occurrence of MDR with mcr-1 E. coli has been reported earlier [9,47], however, rats carrying these types of resistance determinants on plasmids are firstly reported in this study to the best of our knowledge. Occurrence of MDR E. coli carrying ARGs on horizontally transferable elements is worrisome and imposes a potential threat of transferring and disseminating these resistance determinants to human and animals through contaminated food, water and environment.…”
Section: Plos Onementioning
confidence: 50%
“…Occurrence of MDR with mcr-1 E . coli has been reported earlier [ 9 , 47 ], however, rats carrying these types of resistance determinants on plasmids are firstly reported in this study to the best of our knowledge. Occurrence of MDR E .…”
Section: Discussionmentioning
confidence: 68%
“…The isolates belonged to three different serotypes and phylogroups. All the strains were phenotypically resistant to multiple antimicrobials and carried several resistance and virulence genes [ 11 ].…”
mentioning
confidence: 99%